2015
DOI: 10.1007/s11064-015-1676-0
|View full text |Cite
|
Sign up to set email alerts
|

T Cells and Cerebral Ischemic Stroke

Abstract: Stroke results in cerebral inflammation that causes brain injury and triggers immunodepression, resulting in an increased incidence of morbidity and mortality secondary to remote infection. It is well known that T cells modulate brain inflammation after ischemic stroke, and targeting T cells may be an innovative therapeutic strategy for stroke treatment. T cell deficiency is neuro-protective, but the observed protective effects differ between ischemic models. Recent studies suggest different T cell subsets may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 54 publications
1
34
0
2
Order By: Relevance
“…The results of studies on IS suggest the important role of HMGB1 in stroke-induced immunosuppression, which is similar to a phenomenon observed in SAH [28][29][30][31]. The levels of this protein were increased in IS patients and correlated with the number of circulating leukocytes, stroke severity, and inflammatory markers [32].…”
Section: Discussionsupporting
confidence: 67%
“…The results of studies on IS suggest the important role of HMGB1 in stroke-induced immunosuppression, which is similar to a phenomenon observed in SAH [28][29][30][31]. The levels of this protein were increased in IS patients and correlated with the number of circulating leukocytes, stroke severity, and inflammatory markers [32].…”
Section: Discussionsupporting
confidence: 67%
“…Some studies with animal models also indicated that lymphocytes were involved in the pathology following ICH [23], which suggested that lymphocytes have a role in the pathological changes after ICH. Patients with stroke may experience lymphopenia or decreasing absolute lymphocyte count, a phenomenon of immunodepression, which might result from activation of the hypothalamic-pituitary-adrenal system, sympathetic nervous system, and parasympathetic nervous system, via the secretion and release of acetylcholine, catecholamines, and cortisol, which may lead to lymphocyte apoptosis [24]. Some studies suggested that higher ALC can upregulate the anti-inflammatory cytokine interleukin (IL)-10 and suppress inflammatory cytokines including tumor necrosis factor (TNF)-α and IL-6, resulting in a neuroprotective effect [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, just like NLR, LMR is a biomarker reflecting the inflammatory and immune status caused by ICH. The inflammatory response following ICH is meditated by lymphocytes and monocytes, leading to secondary brain injury including white matter damage, blood–brain barrier breakdown, and brain edema [2428,3135], which may have a critical role in the development of ND and 90-day mortality. On the other hand, immunosuppression caused by ICH may led to some post-stroke complications such as pneumonia, which promotes patient mortality [27].…”
Section: Discussionmentioning
confidence: 99%
“…The information described above resolves the controversial issue of whether a lower lymphocyte count is independently associated with poor outcome at 3 months [ 7 , 26 ]. Following stroke, patients may have lymphopenia or a reduction in absolute lymphocyte count, a phenomenon of immunodepression, which might due to activation of the hypothalamic-pituitary-adrenal system, sympathetic nervous system, and parasympathetic nervous system, with the secretion and release of cortisol, catecholamines, and acetylcholine, contributing to lymphocyte apoptosis [ 27 ]. Our study found that patients in group 3 with decreased lymphocyte count were more likely to have poor outcome, which suggests that a lower lymphocyte count is correlated with adverse prognosis of patients undergoing IV rt-PA administration.…”
Section: Discussionmentioning
confidence: 99%